Maman Fish Sdn. Bhd. / Azizi Azuan Abu Bakar … [et al.] - Abu Bakar, Azizi Azuan; Musa, Azham; Minhat, Mohd. Asrul; Sariau, Jaslinah; Kamisan, Mohd. Nazri (2003)
Maman Fish Sdn. Bhd. is the name of our company that has decided to make business in cages fish. This company is a private limited business. Actually, to get involved in this type of business is not quite easy. This is because the cost to do this business is high. In cages fish, we must need at least RM 3.3 million to run this kind of business. For certain people, said that it is a risky one, but for us it is an opportunity that will give us a large amount of profit. In this business we had choose one place that is quite suitable for us. We will run our operation in territorial water near Ketam Island. This island is situated in Selangor. We choose this place because it is near our correspondence address. Besides that we also had our office, which is situated in section 9 Shah Alam Selangor. We choose this business because of the increasing of the request for the fresh fish in Malaysia and South East Asia. Before we start this business, we had survey certain places that had run this business in Malaysia. From the survey we had decided that this is the right business that can make a lot of profit. Furthermore, this business can only make a lot of profit within a year. This is because of the operational are from the hatchery to a large fish that can be sell in over RMiSL-00 per kilo. The future prospect of the business is we hope that this business will succeed. This is because we try to export our fish to other country such as South East Asia, United State of America, and many more. Therefor we hope that we will be the lagers company that export fresh salt water fish in the country.